Optimising female athletic performance - Pinchbeck, J.; Lingam-Willgoss, C.; Rea, S. (Routledge, 2025)
Optimising Female Athletic Performance presents a comprehensive overview of the wide range of factors that underpin female athletic performance based on the most up to date research. This book draws from the disciplines of anatomy, physiology, psychology, and sociology to develop an integrated approach and illustrates how female athletes can be safely prepared for training and performance in a way that benefits their health and optimises their performance. The book covers the specific challenges active females encounter as they move through their lives from childhood, puberty, adolescence, adulthood, potentially motherhood, and on to the menopausal stage.